Trends in gut-heart axis and heart failure research (1993–2023): A bibliometric and visual analysis - Jiahui Ouyang; Lingli Zhao; Yewen Song; Hua Qu; Tianyi Du; Liu Shi; Zhijie Cui; Zhonghui Jiang; Zhuye Gao (Heliyon, 2024)
Background: The incidence of heart failure, the terminal stage of several cardiovascular diseases, is increasing owing to population growth and aging. Bidirectional crosstalk between the gut and heart plays a significant role in heart failure. This study aimed to analyze the gut-heart axis and heart failure from a bibliometric perspective. Methods: We extracted literature regarding the gut-heart axis and heart failure from the Web of Science Core Collection database (January 1, 1993, to June 30, 2023) and conducted bibliometric and visualization analyses using Microsoft Excel, CiteSpace, VOSviewer, and the R package “bibliometrix.” Results: The final analysis included 1646 articles with an average of 35.38 citations per article. Despite some fluctuations, the number of articles published per year has steadily increased over the past 31 years, particularly since 2018. A total of 9412 authors from 2287 institutions in 86 countries have contributed to this field. The USA and China have been the most productive countries, with the Cleveland Clinic in the USA and Charité-Universitätsmedizin Berlin in Germany being the most active institutions. The cooperation between countries/regions and institutions was relatively close. Professor Tang WHW was the most productive author in the field and the journal Shocks published the highest number of articles. ''Heart failure,'' ''gut microbiota,'' ''trimethylamine N-oxide,'' and ''inflammation'' were the most common keywords, representing the current research hotspots. The keyword burst analysis indicated that ''gut microbiota'' and ''short-chain fatty acids'' are the current frontier research topics in this field. Conclusion: Research on the gut-heart axis and heart failure is increasing. This bibliometric analysis indicated that the mechanisms associated with the gut-heart axis and heart failure, particularly the gut microbiota, trimethylamine N-oxide, inflammation, and short-chain fatty acids, will become hotspots and emerging trends in research in this field. These findings provide valuable insights into current research and future directions.